Southern and postcolonial perspectives on policing, security and social order - Cavalcanti, Roxana Pessoa; Squires, Peter; Waseem, Zoha (Bristol University Press, 2023)
Postcolonial legacies continue to impact upon the Global South and this edited collection examines their influence on systems of policing, security management and social ordering. Expanding the Southern Criminology agenda, the book critically examines social harms, violence and war crimes, human rights abuses, environmental degradation and the criminalization of protest. The book asks how current states of policing came about, their consequences and whose interests they continue to serve through vivid international case studies, including prison struggles in Latin America and the misuse of military force. Challenging current criminological thinking on the Global South, the book considers how police and state overreach can undermine security and perpetuate racism and social conflict.